EFFECTIVENESS OF USING INTERACTIVE METHODS IN DIGITAL EDUCATIONAL ENVIRONMENT (Universal International Scientific Journal, 2026)
This article analyzes the pedagogical effectiveness of using interactive methods in a digital learning environment. It highlights the use of electronic tests, online discussions, virtual laboratories, simulations, and gaming technologies in modern educational processes to activate students' cognitive activity, develop independent thinking, and increase motivation for learning. It also substantiates the opportunities for students to develop analytical thinking, problem-solving, communication, and collaboration skills using interactive methods.
Keywords: digital learning environment, interactive methods, pedagogical technologies, electronic tests, virtual laboratory, simulation, online discussion, educational effectiveness, independent thinking, student motivation